Pendidikan Kesehatan Tentang Manajemen Stress Sebagai Upaya Peningkatan Kesehatan Jiwa Pada Remaja Di SMK Suryalaya - Rismawan, Wawan; Marpatmawati, Idhfi; Hidayat, Nandita Milda (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Adolescents are an age group that is vulnerable to stress and has a serious impact on mental health. Pressure, social, and developmental transitions make vocational high school students a high-risk group for mental disorders such as anxiety and depression. Unfortunately, understanding and access to mental health services are still very limited among adolescents. Objective: This study was to improve students' understanding of stress, its impact on health, and stress management techniques through applicable health education at SMK Suryalaya. Method: This activity was carried out through mental health education to 61 students in grades X and XI at SMK Suryalaya, using interactive lecture methods, visual media, and pretest and posttest evaluations. Data were analyzed to see changes in student knowledge before and after the educational intervention. Results: There was an increase in the average score of student knowledge from 8.14 in the pretest to 9.53 in the posttest, with a difference of 1.39 points. Most students who were originally in the "moderate" category moved to the "high" category after the intervention. All participants experienced an increase or maintained their maximum score without a decrease in value. Conclusion: Health education on stress management has been proven to be effective in improving mental health literacy in adolescents. This intervention not only strengthens students' conceptual understanding, but also builds awareness of the importance of managing stress in a healthy way. This activity can be used as a promotive-preventive model for other schools to create a learning environment that supports students' mental health. Keywords: adolescents, stress, stress management, mental health, health education